Attitude and influencing factors to receive the COVID‐19 vaccine among university students in Sichuan Province, China: A cross‐sectional study - Kaihan Yang; Yang Chi; Jiamin Wan; Xuedan Qing; Yubinxin Peng; Hong Chen; Jiehang Li; Xiaolian Jiang (Wiley, 2023)
Abstract Aims To explore the university students' attitude and the potential influencing factors to receive the coronavirus disease 2019 (COVID‐19) vaccine in Sichuan Province, China. Design A cross‐sectional study. Methods The self‐designed questionnaire was distributed among university students online in June 2021. SPSS software was used for statistical analysis of the data. Descriptive statistics, Chi‐square, two independent samples t‐tests, one‐way analysis of variance (ANOVA), multivariate linear regression, and content analysis were performed. Results A total of 397 questionnaires were analysed, involving 316 (79.6%) respondents have received at least one dose of a COVID‐19 vaccine and 81 (20.4%) have not taken the vaccine. The total mean score of university students' vaccination attitude was 25.97 (standard deviation [SD] = 3.720), and the total scoring rate was 74.2%. Main factors influencing students' attitude included education level, major, living style, with chronic disease or not, self‐reported vaccination status, and number of medical units that can provide vaccination within 3 km of residence. Students were more willing to choose Chinese‐manufactured vaccines (66.8%) and participate in collective vaccination programs organized by the school (71.3%). The desired vaccine protection period was 5-10 years (42.1%). The top three reasons for refusing the vaccine or vaccine hesitancy were as follows: concern about the side effects of vaccine (44.8%), lack of information about vaccine (31.0%), and concern about the efficacy of vaccine (29.3%). Conclusion In general, most of the participants had relatively high level of positive attitude to receive the COVID‐19 vaccine. Nevertheless, more attention should be paid to postgraduate students, non‐medical students, those living alone, those with chronic disease, those have not received the COVID‐19 vaccine, and those living far away from the vaccination medical units. Findings of this study can help educational institutions in developing effective interventions to improve the vaccination rate in the university student population.